Fluorescent Chemosensors for Ion and Molecule Recognition: The Next Chapter - Yan, Kai-Cheng; Steinbrueck, Axel; Sedgwick, Adam C.; James, Tony D. (Frontiers in Sensors, 2021)
Over the past 30 years fluorescent chemosensors have evolved to incorporate many optical-based modalities and strategies. In this perspective we seek to highlight the current state of the art as well as provide our viewpoint on the most significant future challenges remaining in the area. To underscore current trends in the field and to facilitate understanding of the area, we provide the reader with appropriate contemporary examples. We then conclude with our thoughts on the most probable directions that chemosensor development will take in the not-too-distant future.